The Nahdlatul Ulama Model In Developing Religious Moderation: Analysis of the Acceptance of the Single Principle of Pancasila and Efforts to Implement it in Indonesia - Halid, Ahmad; Yasaruddin bin Yassir, Muhammad (MAJEMUK Jurnal Pendidikan Agama Islam, 2024)
The Indonesian nation is truly a nation whose character is accommodative, selective, moderate, with the substance (mahiyah) of each being in line. The Indonesian nation is a religious nation and respects differences. The attitude of accepting Pancasila as a fixed price is due to the strong insight and attitude of religious moderation within oneself and the environment so that one of the benefits is accepting Pancasila as the basis of the nation and state. Methods: This research uses a qualitative approach, collecting data through interviews, observations, discussions and literature documents . Results: Pancasila is the philosophy of the Indonesian nation which is the basis for all aspects of the life of the Indonesian nation. Pancasila, a human product, cannot be religious or considered equivalent to religion. Pancasila has five values which are in line with Islamic teachings. Conclusion: first, Ma’lumun min ad-dini bi an-Nadhari wa al-Ijtihad: Called Wadl’iyun Basyariun: made by humans by directing all their rational potential with ijtihad. For example, Pancasila is a human creation that is in the realm of discussion or enters the realm of reason and can be discussed as deeply as possible. Second, Ta’abbudi is called ma’lumun min ad-addini bi ad-dlarurah: It is called Wadl’iyun dewan: made by God. Located in the permanent area. You can’t think about it, for example obligatory prayer, fasting, the pillars of Islam, the pillars of faith, the propositions of the Qur’an, these cannot be included in Wadl’iyun Basyariun.